P173 Efficacy and safety of upadacitinib versus placebo and adalimumab in patients with active PsA and inadequate response to non-biologic DMARDs (SELECT-PSA-1): a double-blind, randomised controlled phase III trial. (26th April 2021) - McInnes, Iain; Anderson, Jaclyn; Magrey, Marina; Merola, Joseph F; Liu, Yi; Kishimoto, Mitsumasa; Jeka, Sławomir; Pacheco-Tena, Cesar; Wang, Xin; Chen, Liang; Zueger, Patrick; Pangan, Aileen; et al.
Abstract: Background/Aims   Upadacitinib (UPA) is a JAK inhibitor under evaluation for PsA treatment. We aimed to assess efficacy and safety of UPA vs placebo (PBO) and adalimumab (ADA) in patients with prior inadequate response (IR) or intolerance to ≥ 1 non-biologic DMARD. This research was previously presented at EULAR; published in Annals of Rheumatic Diseases. Methods   Patients with active PsA (≥3 swollen, ≥3 tender joints), active/historical psoriasis, ≤2 non-bDMARDs were randomized 1:1:1:1 to once-daily UPA 15mg (UPA15), UPA 30mg (UPA30), ADA 40mg every other week, or PBO. Primary endpoint: proportion of patients achieving ACR20 for UPA vs PBO at Wk12. Secondary endpoints: change in HAQ-DI, FACIT-F, SF-36-PCS (Wk12), sIGA of Psoriasis 0/1, PASI75, change in Self-Assessment of Psoriasis Symptoms (Wk16), change in modified Sharp/van der Heijde Score (mTSS), proportion patients achieving MDA, resolution of enthesitis (LEI=0) and dactylitis (LDI=0) (Wk24), non-inferiority and superiority vs ADA for ACR20, superiority for HAQ-DI, patient assessment of pain NRS (Wk12). Additional secondary endpoints: ACR50/70 at Wk12 and ACR20 at Wk2. Treatment-emergent adverse events (TEAEs) through Wk24 reported for patients receiving ≥1 dose of study drug. Results   1, 705 patients were randomised; 1, 704 received study drug (mean age 50.8 yrs, mean duration of PsA diagnosis 6.1 yrs). 82% on ≥ 1 concomitant non-bDMARD. At Wk12, ACR20 rates were 70.6% with UPA15 and 78.5% with UPA30 vs 36.2% with PBO (p < 0.001 for UPA15/30 vs PBO) and 65.0% with ADA (non-inferiority, p < 0.001 for UPA15/30 vs ADA; superiority, p < 0.001 for UPA30 vs ADA). More patients achieved ACR50/70 with UPA15/30 vs PBO and UPA30 vs ADA. Improvements were observed with UPA15/30 vs PBO for all secondary endpoints and for UPA 15/30 vs ADA for HAQ-DI and UPA30 vs ADA for improvement in pain. At Wk24, change in mTSS was 0.25 for PBO, -0.04 for UPA15, 0.03 for UPA30, and 0.01 for ADA (p < 0.001 for UPA15/30 vs PBO). Rates of TEAEs and serious AEs, including serious infections, were similar in PBO, UPA15, and ADA arms and higher with UPA30. Herpes zoster rates were similar for PBO and UPA15/30. No MACE was reported with UPA. One malignancy occurred in both the PBO and UPA15 arms; 3 malignancies were reported in both UPA30 and ADA arms. VTE were reported in 1 PBO patient, 1 UPA30 patient and 2 ADA patients. One death occurred in the PBO arm. Conclusion   In this non-bDMARD-IR PsA population UPA15/30 demonstrated improvement in musculoskeletal symptoms, psoriasis, physical function, pain, fatigue and inhibited radiographic progression; improvements observed by Wk2. At Wk12, UPA15/30 were non-inferior to ADA for ACR20, with superiority demonstrated for UPA30. Greater percentages of UPA vs PBO patients achieved stringent disease control measures (MDA, ACR50/70, sIGA 0/1). No new safety signals were identified compared to the safety profile observed in RA. Disclosure   I. McInnes: Other; I.McI has received research grants and honoraria from Abbvie, BMS, Celgene, Novartis Lilly, Janssen, Pfizer, UCB. J. Anderson: Shareholder/stock ownership; J.A. may be a stock/ shareholder of AbbVie Inc. M. Magrey: Consultancies; M.M. has received consulting fees from Novartis, Eli Lilly, Pfizer, and Janssen. Grants/research support; M.M. has received grants/ research support from Amgen, AbbVie, and UCB Pharma. J.F. Merola: Consultancies; J.F.M. is a consultant for Merck, Abbvie, Dermavant, Eli Lilly, Novartis, Janssen, UCB, Celgene, Sanofi, Regeneron, Arena, Sun Pharma, Biogen, Pfizer, EMD Sorono, Avotres and Leo Pharma. Y. Liu: None. M. Kishimoto: Consultancies; M.K. has received consulting fees from AbbVie, Eli Lilly, Celgene, Pfizer, Gilead, Janssen, and UCB Pharma. Honoraria; M.K. has received honoraria/ speakers fees from AbbVie, Eisai, Celgene, Pfizer, Novartis, Eli Lilly, Tanabe-Mitsubishi, Ayumi, Janssen, Astellas, and UCB Pharma. S. Jeka: None. C. Pacheco-Tena: None. X. Wang: Shareholder/stock ownership; X.W. may be a shareholder of AbbVie Inc. L. Chen: Shareholder/stock ownership; L.C. may be a stock/shareholder of AbbVie Inc. P. Zueger: Shareholder/stock ownership; P.Z. may be a stock/shareholder of AbbVie Inc. A. Pangan: Shareholder/stock ownership; A.P. may be a stock/shareholder of AbbVie Inc. F. Behrens: Honoraria; F.B. has received honoraria and speakers fees from Pfizer, AbbVie, Sanofi, Lilly, Novartis, UCB, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai. Grants/research support; F.B. has received grants/ research support from Pfizer, Janssen, Chugai, Celgene and Roche.